EVOLUTION OF DETERGENTS IN WASTEWATER AND SLUDGE FROM REFINING INDUSTRY OF VEGETABLE OILS AND THEIR ABATEMENT BY COMPOSTING / EVOLUTION DES DETERGENTS DANS LES EAUX USEES ET LES BOUES D’INDUSTRIE DE RAFFINAGE DES HUILES VEGETALES, ET LEUR ABATTEMENT PAR COMPOSTAGE - SLIMANE LAHSAINI; ANAS AGUELMOUS; MOHAMED CHATOUI; LAILA IDRISSI; LOUBNA EL FELS; SALAH SOUABI; MOHAMED HAFIDI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2018)
This research aims to determine the effectiveness of the wastewater treatment plant (WWTP) in removing detergents from Moroccan edible oils unit. The produced sludge was composted with straw and green waste (5:4:1 v/v/v), the mixture allows a dilution of detergents up to 79.11 % compared to fresh sludge alone. The efficiency of the WWTP for removing detergents ranges from 6 to 50 % with an average of 35 % for different samples. However composting has reduced the detergents contained in the sludge with 85.84 % compared to the initial mixture (T0). These results show that the composting of sludge is an efficient technology for the biodegradation of toxic components.